2015
DOI: 10.3233/bmr-140575
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about low back pain: Status quo in Indian general population

Abstract: Prevalence of Low Back Pain was found to be high among the general population sampled and also myths regarding LBP still exist among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…Our results can be compared with a similar study conducted in Pune, India. It studied myths among the general population aged 18-60 years which reported a similar prevalence too [24]. The only difference from their findings was that people agreed to surgery being an important treatment option whereas in our study 55.8% of participants disagreed with this belief.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Our results can be compared with a similar study conducted in Pune, India. It studied myths among the general population aged 18-60 years which reported a similar prevalence too [24]. The only difference from their findings was that people agreed to surgery being an important treatment option whereas in our study 55.8% of participants disagreed with this belief.…”
Section: Discussioncontrasting
confidence: 89%
“…Studies have shown that the presence of false beliefs among individuals contributes to the development of disability associated with LBP [24]. False beliefs associated with LBP lead to overutilization of health care and increased use of advanced imaging, leading to a spiraling increase in healthcare costs [18].…”
Section: Discussionmentioning
confidence: 99%
“…12 The prevalence and consequences of LBP are also seen to be high in low-and middle-income countries, causing a great concern among communities, researchers, and public health program planners in these regions. [13][14][15] Pagare et al 16 indicated that the lifetime prevalence of LBP in the Indian general population was 75%, while a nationwide longitudinal study in Thailand showed that 30% of the study cohorts had a history of LBP in the years 2009 and 2013. 17 A recent study in Brazil also showed that the 1-week prevalence of LBP was 28.8% (39% in males and 60.9% in females).…”
mentioning
confidence: 99%
“…Deyo’s ‘Myths of Back Pain’ questionnaire includes the most common misconceptions encountered in clinical practice of which doctors-in-training should be aware [9]. It has been utilised in multiple studies as a succinct, quick assessment tool of attitudes towards low back pain [1418]. The statements are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%